(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Toni Morrison’ famous novels “The Bluest Eye” and “Beloved” are discussed as the presentation of racism, classicism, sexism, exploitation and suppression of black women in America. The relationship between mother and a daughter exhibits the feminine approach and the slavery system in America.